PENGEMBANGAN EKOWISATA BERBASIS KEANEKARAGAMAN HAYATI DI TAMAN WISATA ALAM GUNUNG TUNAK, LOMBOK TENGAH - Tresnani, Galuh; Suana, I Wayan; Hadi, Islamul; Zamroni, Yuliadi; Suryadi, Bambang Fajar; Sadewo, Imran; Taqwim, Ahsani (Universitas Mataram, 2024)
Ecotourism is a nature-based tourism activity where natural conditions are still natural and generally aims to introduce biological conservation activities. Gunung Tunak Nature Tourism Park (TWA) in Central Lombok is a tourist area that has a wealth of flora and fauna that can be developed as ecotourism. The natural beauty in this area has not yet been developed much, due to the local community's lack of understanding of ecotourism. This community service activity aims to develop interpretive routes within the Gunung Tunak TWA area, provide knowledge about ecotourism and help promote ecotourism in the Gunung Tunak TWA. Service activities are carried out in 4 stages, namely surveying interpretation routes and unique flora and fauna, creating interpretation routes and route maps, counseling and creating promotional media. This community service activity has run smoothly thanks to the very cooperative cooperation of partners in discussion forums and the creation of signboards and interpretation paths. Mount Tunak TWA has potential fauna for ecotourism in the form of birds, mammals, reptiles and insects. Animal information signs on the Bilasayak and Teluk Ujung interpretation routes have been created to help tourists find wildlife that can be observed on Mount Tunak.